Images, Imaginaries, and Insurgencies: Abolition Feminism and Research-Creation - Yao, Helen (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
This article explores the relationship between research-creation, abolition feminism, scholar-activism, and emancipatory pedagogy. Research-creation, as a scholarly practice that transgresses disciplinary boundaries and institutional classifications, rejects dispossession and alienation. The abolition feminist notion of a “jailbreak of imagination” (Kaba 2021) is exemplified in the ontological and epistemological foundations of research-creation. Reflecting upon my experiences producing and publishing abolition feminist research-creation projects, I use this article to demonstrate the synergistic potentials between the two bodies of scholarship. As I narrate how abolition feminist scholarship takes form through research-creation, I strive to articulate the possibilities and limits that come with creating an abolition feminist method.